Effectiveness of Investigator Certification in Improving Special Crime Investigation Quality at Bengkulu Police - Sonny Wibisono; Rineke Sara (al-Battar: Jurnal Pamungkas Hukum, 2025)
This study aims to analyze the effectiveness of investigator and assistant investigator certification as a mandatory instrument for improving the quality of special criminal investigations at the Directorate of Special Criminal Investigation of the Bengkulu Regional Police. The research employs a normative juridical method using statutory and conceptual approaches by examining the Criminal Procedure Code (KUHAP), Law No. 2 of 2002 on the Indonesian National Police, Perpol No. 6 of 2019 on Criminal Investigation, and Perkap No. 99 of 2020 on the development of superior police human resources. The findings demonstrate that certification significantly enhances investigator competence, professionalism, and compliance with procedural law, which is reflected in more complete case files, higher procedural accuracy, and increased success rates in achieving the P-21 stage. Certified investigators also show stronger legal reasoning in case handling and investigation termination decisions. However, the effectiveness of certification is constrained by limited certified trainers and assessors, unequal distribution of certified investigators, and weak integration of competency supervision among internal units. The study concludes that investigator certification is an effective legal and managerial instrument to improve investigation quality, provided it is supported by strengthened internal regulations, digitalized training and assessment systems, and an integrated performance-based evaluation framework.